2015
DOI: 10.5999/aps.2015.42.4.407
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Locations of Facial Injury and the Use of Bicycle Helmets: A Systematic Review

Abstract: The aim of this study is to review the protective effect of a bicycle helmet on each facial location systematically. PubMed was searched for articles published before December 12, 2014. The data were summarized, and the odds ratio (OR) between the locations of facial injury was calculated. A statistical analysis was performed with Review Manager (The Nordic Cochrane Centre). Bicycle helmets protect the upper and middle face from serious facial injury but do not protect the lower face. Non-wearers had significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 7 publications
2
17
0
1
Order By: Relevance
“…Therefore, the probability of a mid-facial fracture is much higher. The same mechanism was described by Hwang et al in a review from 2015 (10). In case-control studies performed by Thompson et al (9, 12, 13, 33), the helmet was found to exert also a protective effect on the upper and mid-face in 65% of cases.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Therefore, the probability of a mid-facial fracture is much higher. The same mechanism was described by Hwang et al in a review from 2015 (10). In case-control studies performed by Thompson et al (9, 12, 13, 33), the helmet was found to exert also a protective effect on the upper and mid-face in 65% of cases.…”
Section: Discussionsupporting
confidence: 64%
“…The main outcome was that helmets decrease the risk of facial injury to the upper and mid face by 65% (9). A present review from 2015 performed by Hwang et al showed that a bicycle helmet covers the upper and middle face from serious facial injury but cannot cover the lower face (10). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Precautions such as protective helmets aim to limit the threat of injury. Many studies have shown the proven benefits of wearing protective helmets 2345. Specifically, many studies have shown that helmets reduce the odds of head and brain injuries by 63 to 88% and reduce the odds of upper and midface injuries by 65% in bicyclists 2.…”
mentioning
confidence: 99%
“…Also, they do not protect the lower facial region. 11,12 Not every type of bicycle helmet protects in the same way. Sometimes cyclists with helmets increase their speed and have decreased risk perception and because of that the safety effect can be counterproductive.…”
mentioning
confidence: 99%